Early prediction of pulmonary outcomes in preterm infants using electrical impedance tomography - Gaertner, Vincent D.; Mühlbacher, Tobias; Waldmann, Andreas D.; Bassler, Dirk; Rüegger, Christoph M. (Frontiers in Pediatrics, 2023)
Introduction Electrical impedance tomography (EIT) allows assessment of ventilation and aeration homogeneity which may be associated with respiratory outcomes in preterm infants. Methods This was a secondary analysis to a recent randomized controlled trial in very preterm infants in the delivery room (DR). The predictive value of various EIT parameters assessed 30 minutes after birth on important respiratory outcomes (early intubation <24 hours after birth, oxygen dependency at 28 days after birth, and moderate/severe bronchopulmonary dysplasia; BPD) was assessed. Results Thirty-two infants were analyzed. A lower percentage of aerated lung volume [OR (95% CI) = 0.8 (0.66–0.98), p=0.027] as well as a higher aeration homogeneity ratio (i.e. more aeration in the non-gravity-dependent lung) predicted the need for supplemental oxygen at 28 days after birth [9.58 (5.16–17.78), p=0.0028]. Both variables together had a similar predictive value to a model using known clinical contributors. There was no association with intubation or BPD, where numbers were small. Discussion In very preterm infants, EIT markers of aeration at 30 minutes after birth accurately predicted the need for supplemental oxygen at 28 days after birth but not BPD. EIT-guided individualized optimization of respiratory support in the DR may be possible.